Development of a Model of Japanese Language Learning and Teaching Management in Rajabhat Universities: การพัฒนารูปแบบการบริหารจัดการการเรียนการสอนภาษาญี่ปุ่นในมหาวิทยาลัยราชภัฏ - Juntawongsri, winess (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This purposes of this study were to: 1) investigate the condition and problems of Japanese language learning and teaching management in Rajabhat Universities, 2) develop the Japanese language learning and teaching management model in Rajabhat Universities, and 3) study the effectiveness of the developed model.The findings indicated that 1) lecturers rated the condition of learning and teaching management in Rajabhat Universities in overall at a high level. When considered in each aspect, it was found that all aspects were rated at a high level except the aspect of the facilitators was rated at a moderate level.However the problems of learning and teaching management in overall and all aspects were rated at a moderate level except the aspect of curriculum was rated at a high level. The students rated the condition in overall and each aspect at a high level except the aspect of facilitators was rated at a moderate level.Moreover they rated the problems in overall and each aspect at a moderate level. 2) The developed Japanese language learning and teaching management model in Rajabhat Universities consisted of curriculum, lecturers, students, teaching and learning procedures,measurement and evaluation, and facilitators. Moreover, the administrators and lecturers rated the appropriateness of the developed model at the highest level and possibility in practice at a high level and higher than the set criterion at the significant level of .01. And 3) the results of implementation found that both lecturers and students satisfied with the developed model at the highest level and higher than the set criterion at the significant level of .01